Evaluating the Influence of Policy Certainty and Violence on Coverage of Policy Issues in Pakistani Media - Khan, Jamal Ud Din; Dr. Rooh ul Amin Khan; Dr. Shabir Hussain (Journal of Peace, Development and Communication, 2021)
This article examines the government and press relationship in the context of foreign policy related issues in Pakistan, where the nature of [policy]issues are subjected to frequent changes. The content analysis of three selected issues reflects the existence of soft relationship between media and government in the [violent]issue of Kashmir and Salala check post attack while the policy uncertainty in the issue to join the Saudi Arab led military coalition, instead of soft relations, triggered, comparatively more critical coverage in the selected newspapers- Dawn and The News.